Micro-reservoir depth determination with Twyman-Green Interferometer - Wan Mokhdzani, Wan Nor Haimi; Poopalan, Prabakaran, Assoc. Prof. Dr.; Retnasamy, Vithyacharan; Mohd Naim, Haron (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.